Conivaptan and its role in the treatment of hyponatremia - Ghali, Jalal K (Dove Medical Press, 2009)
Hyponatremia is the most common electrolyte abnormality in hospitalized patients and is associated with increased morbidity and mortality. The recognition of the central role that arginin vasopressin plays in the pathogenesis of hyponatremia and the discovery that its actions are mediated by stimulation of V(1A) and V(2) receptors have led to the development of a new class of drugs, the arginin vasopressin antagonists. Conivaptan is a nonselective V(1A) and V(2) receptors antagonist that was the first of this class to be approved by the FDA for the management of euvolemic and hypervolemic hyponatremia. Its short-term safety and efficacy for the correction of hyponatremia have been established by multiple double-blind, randomized, controlled studies. Blocking the effects of arginin vasopressin on V(2) receptors produces aquaresis – the electrolyte-sparing excretion of water – an ideal approach to correct hypervolemic hyponatremia. The nonselectivity of conivaptan offers a theoretical advantage for its use in heart failure that may merit further exploration.